Seed conservation methods and evaluation of germination rate in Baccharis dracunculifolia DC. (Asteraceae) - Santos, C. D. L. (2016)
Baccharis dracunculifolia, a Brazilian native plant, is an economically important species, as it is the main botanical source of southeastern Brazilian propolis, known as green propolis. We examined the germination rate of B. dracunculifolia seeds that were newly collected, submitted to medium-term storage conditions (6 degrees C, original moisture content), or to long-term storage conditions (-20 degrees C, moisture content reduced to 3%) to verify the viability of its genetic conservation in seed bank. The seeds were germinated in controlled conditions (paper with nystatin 500 UI L-1, 20 degrees C, 12-h photoperiod) and in seedling substrate (at greenhouse) in four replicates of 25 seeds each. The germination rate of newly collected seeds was 50% and the highest rate found was 68% after nine months of medium-term storage conditions. Seeds subjected to long-term storage conditions showed 49% germination rate, statistically equal to the newly collected seeds rate (p <= 0.05). In order to allow conservation of the B. dracunculifolia seeds' characteristics, which in turn enables greater production of green propolis, understanding medium and long-term storage is key. This is also vital for preserving seedlings for reforestation.